Fabrication and microscopic optical characterization of metal-oxide based nanostructures - Yan, Bin (2011)
To date, low-dimensional metal-oxide nanomaterials have attracted intense interests of a great many researchers. In order to better explore the function of such nanostructures in technological applications, it is necessary to understand their characteristics. Most current researches are based mainly on ensemble-averaged measurements, where a large number of nanomaterials are studied and the average responses are recorded. These experiments yield only polydisperse-collective effects, which very often are different from the intrinsic or fundamental properties of the nanomaterials. Some unique properties of nanomaterials cannot be observed because of the large variations in particle shape, orientation, size, and surface defects. The main goal of this research is to fabricate and test the physical properties of individual nanostructures. In this dissertation, several metal-oxide nanostructures, V2O5 nanoribbons, MoO3 nanoflakes, ZnO nanowires and Fe2O3 nanoflakes are fabricated via the thermal evaporation method. The physical, especially optical, properties are investigated by the micro-photoluminescence and Raman scattering techniques. Waveguiding effects and morphology-induced anomalous polarized Raman properties are investigated on waveguiding V2O5 nanoribbons. By controlling the orientational arrangement of MoO3 nanoflakes, we demonstrate the anisotropic electrical/optical properties and edge-preferred defect distributions. Local exciton-longitudinal optical phonon interaction in a single ZnO nanowire is suppressed by mechanical deformation. In addition, we proposed a mechanism to elucidate the ultraviolet induced change of surface wettability of ensembled Fe2O3 nanoflakes.